Geothermal index variation )LST( Between the Karkh and Rusafa sides of the city of Baghdad and the factors affecting it for the year 2023 (Journal of the College of Basic Education, 2025)
As a result of climate change and urban sprawl at the expense of agricultural lands, the ground temperature index (LST) has increased, Especially in urban areas. Therefore, This research came to reveal the difference in the ground temperature index (LST) between the Karkh and Rusafa sides of Baghdad city for the year 2023 using satellite data by employing spectral indicators and the outputs of the broad analytical capabilities of geographic information systems (GIS). Therefore, a satellite image from the 8_Land OLI sat satellite was chosen in 2023, to monitor the Land Surface Temperature Index (LST), the NDVI Vegetation Index, and the NDBI Normalized Variability Index. These two indicators are among the most influential indicators on global temperature. The highest values ​​of the geothermal temperature index (LST) were in the Karkh side (55.39-63.57), while the lowest values ​​of the geothermal temperature index (LST) were (39.01-47.19). As for the Rusafa side, the highest values ​​of the geothermal temperature index (LST) reached (55.64_63.82), while the lowest values ​​of (LST) reached (39.26_47.44). Thus, the Rusafa side recorded higher LST values ​​than the Karkh side in the upper and lower limits. As for the vegetation index, the highest (NDVI) vegetation index was recorded on the Karkh side (0.196_0.515), while the lowest (NDVI) vegetation index values ​​were recorded (-0.144_0.107). As for the Rusafa side, the highest values ​​of the NDVI (Natural Domestic Viability Index) were recorded (-0.19_0.51), while the lowest values ​​of the NDVI (Natural Domestic Viability Index) reached (-0.19_0.089). As for the standard deviation index (NDBI), this index reached (-0.015_0.51) in the Karkh side, while the lowest level of this index reached (-0.38_-0.093). As for Al-Rusafa, the highest level of this indicator reached (0.0071_0.46), while the lowest level reached (-0.081_-0.33). As for the process of modeling the NDVI vegetation index with the LST (Land Surface Temperature Index) in both the Karkh and Rusafa sides, the highest LST (Land Surface Temperature Index) rate was recorded for the Karkh side (59.02) °C. The lowest temperature reached (42.80)°C. As for the Rusafa side, it recorded an average of (60.23)°C, while the lowest average recorded (43.40)°C. Thus, the average ground temperature index (LST) for the Rusafa side recorded a higher value than that for the Karkh side, within the upper and lower limits of the (NDVI) ranges. As for the modeling of the geothermal temperature index (LST) with the normalized variance index (NDBI) for the Karkh and Rusafa sides, the highest rate of the LST index was recorded in the Karkh side, reaching (59.18)°C. The lowest temperature reached (43.15)°C. As for the Rusafa side, the highest rate of the geothermal temperature index (LST) within the normalized variation index (NDBI) was recorded at (60.65)°C, and the lowest rate reached (43.70)°C. Accordingly, the LST index rate for the Rusafa side recorded a higher value than that for the Karkh side, within the upper and lower limits of the NDBI index ranges